Estudio biodirigido en hojas de Annona muricata en la búsqueda de extractos con efecto vasorrelajante en anillos de aorta aislados de rata - Ruiz Romero, Dulce María (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
Arterial hypertension (AHT) is the principal risk factor for develeping cardiovascular, renal and cerebrovascular diseases . The drugs used for the treatment of hypertension is effectivy in half of the cases, nevertheless there are several factors that affect the control of hypertension. Because of that it is necessary to search for new sources of compounds that help to manage this disease. A sourse of new compounds is found in medicinal plants, jus like Annona muricata, that has been used in traditional medicine to treat different kind of diseases, like hypertension, and this use is well documented. In the present work was evaluated his vasorelaxant effect. A bioguided study was performed to elucidate the effect of the extract and the compounds responsible for their activity. The hexane, dichloromethane and methanol extracts were obtained with successive maceration of the leaves with the solvent until components were exhausted and concentrated in rotavapor. The vasorrelaxan effect of the extracts was evaluated in rat aortic ring with the aisolated organ method, the concentration used for the extracts was 0,025 mg/ml and 0,05 mg/ml. the extract that showed the greatest vasorrelaxant activity was selected. Also the effect of graded doses of the extract with the major activity was evaluated (0,01-0,05 mg/ml) in aortic rings of rats treated with the eNOS inhibitor, L-NAME. The metanolic extract at a concentration of 0,025 mg/ml had the greatest activity because it relax the aortic rings of normotensive and hypertensive rats, and this vasorelaxation was concentration dependent. The metanolic extract was analyzed by thin layer chromatography and by ultra violet spectroscopy and it was found to contain flavonoids, which can be responsible of the vasorelaxant activity.

La hipertensión es el principal factor de riesgo para desarrollar enfermedades cardiovasculares, renales y accidentes cerebrovasculares. La medicación que existe para el tratamiento es efectiva en la mayoría de los casos, sin embargo existen diversos factores que afectan su control, por lo que surge la necesidad de buscar fuentes de nuevos compuestos que ayuden al manejo de la hipertensión. Una fuente de nuevos compuestos se encuentra en las plantas, tal como Annona muricata cuyo uso en la medicina tradicional está ampliamente reportado. En la presente investigación se evaluó su efecto vasorrelajante. Un estudio biodirigido se realizó para dilucidar el extracto y los posibles grupos de compuestos responsable de ésta actividad. Los extractos hexánico, diclorometánico y metanólico se obtuvieron de las hojas por maceración sucesiva con el solvente hasta agotar componentes y se concentró en rotavapor. El efecto vasorrelajante de los extractos se evaluó en anillos de aorta por el método de órgano aislado con una concentración de los extractos de 0,025 mg/ml y 0,05 mg/ml. El extracto con mayor efecto vasorrelajante se seleccionó. Se evaluó el efecto de la concentración del extracto con mayor actividad vasorrelajante (0,01-0,05 mg/ml) en un modelo de rata hipertensa inducida por L-NAME. El extracto se analizó por cromatografía en capa fina y por espectrofotometría UV. El extracto metanólico a la concentración de 0,025 mg/ml tuvo la mayor actividad al relajar los anillos de aorta de ratas normotensas e hipertensas, y el efecto del extracto es concentración dependiente. Se encontró que el extracto posee compuestos del tipo flavonoide, los cuales pueden ser los responsables de la actividad vasorrelajante.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2017-0546; Hipertensión; Vasorrelajante; Aorta de rata; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3941